Inhibition of lncRNA RET enhances radio-sensitivity of tumor cells via miR-3179/Slug/PTEN axis. Issue 2 (1st April 2022) - Liang, Xinxin; Li, Xueping; Wang, Ping; Chen, Zhongmin; Yan, Ziyan; Ao, Xingkun; Liu, Yuhao; Zhu, Jiaojiao; Xi, Tingting; Zhou, Shenghui; Li, Zhongqiu; Li, Chao; et al.
Abstract: Radioresistance is one of the key obstacles that may lead to the failure of cancer treatment. The underlying mechanisms of radioresistance remain largely unknown; however, increasing evidence has shown that long noncoding RNAs (lncRNAs) are involved in radiotherapy resistance of several cancers. In the present study, we demonstrated that radiation-elevated transcript (RET), a newly identified lnRNA, was highly expressed in cancer cells. Knockdown of RET significantly inhibited the proliferation and colony formation of cancer cells and markedly inhibited apoptosis. Furthermore, downregulation of RET in cancer cells significantly inhibited cell growth, decreased colony survival fractions, and promoted apoptosis in response to radiation treatment, indicating a role in radiation resistance. Moreover, RET knockdown significantly increased the expression of γ-H2AX, an indicator of DNA double strand damage, and reversed radiation-induced EMT, both of which contributed to its radiation resistance. In addition, a negative correlation was found between the expression of RET and PTEN. Rescue assays confirmed RET knockdown enhanced radiosensitivity of cancer cells by upregulating the expression of PTEN. Mechanistically, RET positively regulated Slug, a repressor of PTEN transcription, by acting as a molecular sponge of miR-3179. Our present study showed that RET conferred radioresistance by regulating miR-3179/Slug/PTEN axis, indicating that RET may be a potential target for the clinical application in cancer patients with radioresistance.